2003
DOI: 10.1302/0301-620x.85b6.13909
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock-wave treatment for tennis elbow

Abstract: he efficacy of extracorporeal shock-wave therapy for tennis elbow was investigated using a single fractionated dosage in a randomised, double-blind study. Outcomes were assessed using the Disabilities of Arm, Shoulder and Hand questionnaire, measurements of grip strength, levels of pain, analgesic usage and the rate of progression to surgery. Informed consent was obtained before patients were randomised to either the treatment or placebo group. In the final assessment, 74 patients (31 men and 43 women) with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 4 publications
4
49
0
8
Order By: Relevance
“…Buchbinder et al 58 performed searches up to and including February 2005. A total of 10 RCTs were included in their review, [84][85][86][87][88][89][90][91][92][93] with nine RCTs [85][86][87][88][89][90][91][92][93] (1006 participants) comparing ESWT with placebo and one 94 comparing ESWT with a steroid injection (93 participants). Data from six trials were pooled.…”
Section: Electrocorporeal Shock Wave Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Buchbinder et al 58 performed searches up to and including February 2005. A total of 10 RCTs were included in their review, [84][85][86][87][88][89][90][91][92][93] with nine RCTs [85][86][87][88][89][90][91][92][93] (1006 participants) comparing ESWT with placebo and one 94 comparing ESWT with a steroid injection (93 participants). Data from six trials were pooled.…”
Section: Electrocorporeal Shock Wave Therapymentioning
confidence: 99%
“…87,89,90,95 Results from two placebo-controlled trials could not be pooled because of inadequate reporting of results. 91,93 Further information is available in the Cochrane review of ESWT for LET (published online 2005). 96 Electrocorporeal shock wave therapy compared with placebo The nine placebo-controlled trials [85][86][87][88][89][90][91][92][93] reported conflicting results, with three trials [85][86][87] reporting significant differences in favour of ESWT for pain and function, whereas four trials reported no benefit of ESWT over placebo for these outcomes.…”
Section: Electrocorporeal Shock Wave Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In our study this sort of complication did not occur as this is abiologic form of treatment. Extracorporial shock wave therapy was shown to be no better than placebo in a recent study 18 .in present day orthopaedics biological treatment modalities are gaining popularity.bone morphogenic protin and other growth factors have been studied in vitro and presently are being tested in vivo also 19 .the study by Edwards and calandrucciio showed that 22/28 pts responded to autologous blood injection 20 .we used autologous plasma instead of blood to decrease the volume of injection and also to avoid the deposition of iron locally following breakdown of Rbcs .Mishra and pavelko introduced platelet rich plasma technique in the treatment of chronic elbow tendonitis. 21 klein et al 23 reported in their study that TGF ß increase type 1 collagen production in tendon sheath fibroblasts.these mechanism may be work in our study also.further study of autologous plasma versus whole blood or steroid should also be performed in the future.the data suggests autologous plasma may be an alternative to surgery in patients with this disorder of its kind.To conclude the use of autologous plasma injection method provides biologic healing and is an effective solution for refractory lateral epicondylitis of humerus and similar disorders.…”
Section: Discussionmentioning
confidence: 99%
“…국소화된 냉요법이 도움이 될 수 있 으며, 직류전기 자극용법이 통증을 완화 시킬 수 있다 5,7,8,13) . 이온 삼투 요법 또한 통증 완화에 사용될 수 있 지만, 이중 맹검 위약-대조군 연구에서는 효과가 의미 없는 것으로 보고된 바 있다 16) . 혈소판 풍부 혈장은 말 초혈액에 비해 5~10배 농축된 양의 혈소판을 함유 하 고 있으며, 혈소판 내에는 여러 성장인자 (growth factor)를 비롯하여 손상된 조직의 회복 및 재생에 필 요한 생활성화 인자가 풍부하게 포함되어 있다 15) .…”
Section: 서 론unclassified